Microclimate and tree canopy cover: The case of two areas in Núcleo Maraba Pioneira - Pará - Júnior, Antônio Pereira; Jesus, Edmir dos Santos; Bastos, Milka Beatriz Faval; Santos, Rafael Victor Castro (Revista Ecologia e Nutrição Florestal - ENFLO, 2016)
Studies of the urban climate involve numerous climatic variables, such as temperature, air humidity and vegetation. The objective of this research was to determine the trend of two meteorological variables (air temperature relative humidity), in relation to the arborization, sensation and thermal hygrometric perception of the population in the microclimate of two areas (A1 = Avenue Antônio Maia; A2 = Street 5 de Abril) Core Marabá Pioneira. For the measurement of temperature and humidity of the air, the methodology recommended by the Agronomic Institute of Campinas (IAC), adapted for the schedules and collection numbers, was applied. To obtain data on thermal comfort, seventy mixed forms were applied for two consecutive days at 12 hours. The thermal sensation was classified per the contained in the Predicted Mean Vote (PMV) and the discomfort, with the Thom Discomfort Index (ID). Twelve daily readings (6:00 a.m. to 5:00 p.m.) were carried out at each hour in the four meteorological shelters (two in each area) during 23 days of July 2015. The results indicated that the air temperature has tendencies to elevation, The relative humidity of the air, presents opposite tendency. The thermal sensation is very hot (+3), the satisfaction with shading was classified as good (A2 = 50%) and regular (A1 = 41.67%), thermal comfort (A1 = 28.76 °C; A2 = 27.70 ºC), ranges from uncomfortable to very uncomfortable. Therefore, there is a need to improve afforestation in the Marabá Pioneira Nucleus, in order to reduce the discomfort index and the quality of life of the population.